Understanding the relationships between online entrepreneurs' personal innovativeness, risk taking, and satisfaction: Comparison of pure-play and click-and-mortar. Issue 2 (3rd April 2017) - Lian, Jiunn-Woei; Yen, David C.
ABSTRACT: The purpose of this study is to investigate the effects of personal innovativeness and risk taking on online entrepreneurs' satisfaction. Two types of online entrepreneurs (pure-play and click-and-mortar) are compared and contrasted. Specifically, our study investigates the effect of personal innovativeness and risk-taking propensity on the satisfaction of online entrepreneurs, and compares the similarities and differences among varying types of online entrepreneurs. A survey of online entrepreneurs conducted in Taiwan, a country characterized as good for small and medium enterprises entrepreneurship and as having substantial e-commerce development, indicates that personal general innovativeness has a significant positive effect on personal information technology innovativeness (the entrepreneur's level of innovation regarding information technology), entrepreneurial satisfaction, and life satisfaction. Entrepreneurs' life satisfaction also determined by their degrees of entrepreneurial satisfaction. Finally, risk-taking propensity significantly influences entrepreneurial satisfaction for pure-play entrepreneurs only. The results can be referenced by other countries in general, and Chinese regions in particular.